Self-efficacy, stress and sales productivity: the case of Latin American industrial sales executives - Bullemore, Jorge (2021)
Despite advances in research in the area of ??industrial sales, in Latin America these have been scarce. Even more so in those related to aspects such as self-efficacy, stress and sales productivity, which is nil. The line that divides the work and personal lives of workers is increasingly blurred, and in particular of salespeople who work longer hours, perform multiple tasks, and many times report feeling increasingly overwhelmed by their work. This research studies the effect of work overload and self-efficacy on the business productivity of Latin American industrial sales executives. A quantitative investigation was developed with a sample of 149 vendors using constructs with established scales, in turn, confirmatory factor analysis was used, and the model parameters were estimated using the maximum likelihood method. It was concluded for the case study, self-efficacy is negatively related to work stress, and this is negatively related to business productivity. Therefore, self-efficacy is positively related to sales productivity. Finally, the results of the study and its limitations are discussed.